Geometric Constraint Programming (GCP) Implemented Through GeoGebra to Study/Design Planar Linkages - Raffaele Di Gregorio; Tommaso Cinti (Machines)
In the study and design of planar mechanisms, graphical techniques for solving kinematic analysis/synthesis and kinetostatics problems have regained interest due to the availability of advanced drawing tools (e.g., CAD software). These techniques offer a deeper physical understanding of a mechanism’s behavior, which can enhance a designer’s intuition and help students develop their skills. Geometric Constraint Programming (GCP) is the term used to describe this modern approach to implementing these techniques. GeoGebra is an open-source platform designed for the interactive learning and teaching of mathematics and related STEM disciplines. It offers an object-oriented programming language and a wide range of geometric tools that can be leveraged to implement GCP. This work presents a systematic technique for studying and designing planar linkages, based on Assur’s groups and GeoGebra’s tools. Although some kinematic analyses and syntheses of planar linkages using GeoGebra have been previously introduced, the proposed systematic approach is novel and could serve as a guide for implementing similar problem-solving methods in other graphical environments. Several case studies will be presented to illustrate this novel approach in detail.